Catecholic alkaloid sulfonates and aromatic nitro compounds from Portulaca oleracea and screening of their anti-inflammatory and anti-microbial activities. (January 2021) - Hu, Shuiyao; Chai, Wern Chern; Xu, Lintao; Li, Shaoqiang; Jin, Cuirong; Zhu, Rongxiu; Yang, Luping; Zhang, Ranran; Tang, Kaijun; Li, Ping; Yang, Erlan; Chang, Wenqiang; et al.
Abstract : Acidic compounds were enriched from a water decoction of Portulaca oleracea using 717 anion exchange resin column chromatography. A total of 22 compounds including 9 catecholamine derivatives, of which six were rare sulfonic acid derivatives, and 9 nitro derivatives, were further isolated through various column chromatographic methods, and their structures were elucidated by interpreting their spectroscopic data and ECD calculations. Among them, 16 compounds were isolated from P. oleracea for the first time, 8 of which were undescribed compounds and four compounds were natural products. Pharmacological screening indicated that cis -3-(3-nitro-4-hydroxyphenyl)-methyl acrylate exhibited anti-inflammatory activity, measured as inhibition of nitric oxide production in LPS-stimulated RAW264.7 macrophage cells, with an EC50 value of 18.0 μ M, The compounds showed only weak anti-microbial activity with (2 R )-(+)-2-chloro-3-(3-nitro-4-hydroxyphenyl)-propionic acid methyl ester inhibiting Candida albicans with a MIC of 256 μ g/mL, and 3-methoxy-4, 5-dinitrophenol inhibiting Shigella sonnei with a MIC of 512 μ g/mL. Graphical abstract: Image 1 Highlights: Rare catecholic alkaloid sulfonates and nitro compounds were isolated from Portulaca oleracea. A 717 anion exchange resin was applied in enriching rare acidic compounds from water decoction of P. olerace a . Nitro compounds are anti-inflammatory agents and some exhibit weak anti-microbial activity.